Application of Behavioristic Learning Theory in Developing Healthy Life Behavior For student - Elly Zumailah; Tajuddin Nur; Astuti Darmiyanti (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Behavioristic is an effort and learning process that aims to shape students towards the desired life behavior. In the order of implementation, behaviorism can be applied in fostering healthy living behavior through the provision of stimuli which in turn will produce a controlled and directed response. The purpose of this study was to describe the implementation of behavioristic theory in fostering healthy living behavior of Raudhatul Athfal Miftahul Falah students. This study uses a qualitative method with a case study approach. The research data were collected by using observation, interview, and documentation techniques. Data were analyzed through (3) three flow of activities, namely data reduction, data display, and formulation of conclusions. The validity of the data was carried out with two criteria, namely persistence of observation and triangulation including source triangulation and technical triangulation. The results show that school programs to develop healthy living behavior in students are the My Clean School Program, My Healthy School, the School Trash Can Program and the Clean Friday Program. Stimulus provided by school personnel includes giving examples, advice and warnings, as well as giving gifts. Students respond positively and produce changes in students' mindsets who love the environment more and change in behavior, namely getting used to throwing garbage in its place